2020
DOI: 10.15766/mep_2374-8265.10933
|View full text |Cite
|
Sign up to set email alerts
|

MINdI: Mindfulness Instruction for New Interns

Abstract: Introduction Trainee burnout has reached epidemic proportions and is increasing among physicians compared to non-health care professionals. Burnout is associated with depression and lower empathy, poor patient adherence to medical plans, and early physician retirement. Mindfulness is the quality of being nonjudgmental and present and has been shown to decrease physician burnout. Implementation of mindfulness curricula may decrease trainee burnout. Methods Using Kern's s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Virtual curricula consisting of online videos, live instruction, and self-study modules were found to be effective in promoting well-being in physician assistants, interns, residents, and attendings at both community and academic health centers. 44-48 Additionally, medical students have shown interest in learning and practicing mindfulness during clinical rotations. 49 Rac & Chakravarti 50 have proposed eight recommendations on how to integrate mindfulness practices for education and student benefit into the medical school curriculum.…”
Section: Discussionmentioning
confidence: 99%
“…Virtual curricula consisting of online videos, live instruction, and self-study modules were found to be effective in promoting well-being in physician assistants, interns, residents, and attendings at both community and academic health centers. 44-48 Additionally, medical students have shown interest in learning and practicing mindfulness during clinical rotations. 49 Rac & Chakravarti 50 have proposed eight recommendations on how to integrate mindfulness practices for education and student benefit into the medical school curriculum.…”
Section: Discussionmentioning
confidence: 99%
“…A 6-step approach to curricular design informed the development of MINdI . The MINdI curriculum easily integrates into existing 1-hour didactic time ubiquitous among training programs and requires no additional facilitator training .…”
Section: Methodsmentioning
confidence: 99%
“…A 6-step approach to curricular design informed the development of MINdI . The MINdI curriculum easily integrates into existing 1-hour didactic time ubiquitous among training programs and requires no additional facilitator training . Intervention programs received the MINdI facilitator manual and all necessary curriculum implementation supplies.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation